Pan-Cancer Analysis of Oncogenic Role of RAD54L and Experimental Validation in Hepatocellular Carcinoma - Zhou Y; Qiu C; Fu Q; Li T; Zhang X; Zhu C; Qin X; Wu B (Dove Medical Press, 2023)
Yongzhen Zhou,1,2,* Chenjie Qiu,3,* Qingsheng Fu,2 Tao Li,1 Xudong Zhang,1 Chunfu Zhu,1 Xihu Qin,1 Baoqiang Wu1,2 1Department of General Surgery, the Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, Changzhou, 213000, People's Republic of China; 2Graduate School, Bengbu Medical College, Bengbu, 233003, People's Republic of China; 3Department of General Surgery, Changzhou Hospital of Traditional Chinese Medicine, Changzhou, 213000, People's Republic of China*These authors contributed equally to this workCorrespondence: Baoqiang Wu, Email yddf999@163.comBackground: RAD54L is a prominent member of the SWI2/SNF2 protein family, primarily involved in the homologous recombination repair (HRR) process, thereby playing a pivotal role in the repair of DNA double-strand breaks (DSBs). RAD54L has been implicated in the development of numerous tumors. Consequently, we aimed to investigate the potential contribution of RAD54L in pan-cancer.Methods: Various databases and analytical tools were employed for bioinformatics analysis. Moreover, in vitro experiments were conducted to corroborate the findings from the bioinformatics analysis and delve deeper into the role of RAD54L in hepatocellular carcinoma (HCC).Results: RAD54L expression demonstrated a significant elevation in the majority of tumors, and its overexpression was strongly associated with unfavorable survival outcomes. RAD54L displayed robust correlations with the infiltration levels of various immune cells, including cancer associated fibroblasts (CAFs), endothelial cells, and myeloid-derived suppressor cells (MDSCs). Additionally, associations were observed between RAD54L and key factors such as tumor mutation burden (TMB), microsatellite instability (MSI), multiple immune checkpoints, and immune cell infiltration. Moreover, a close relationship was observed between RAD54L expression levels in HCC and clinicopathological characteristics, as well as immune cell infiltration. Experimental techniques including qRT-PCR, Western blotting, colony-forming, Cell Counting Kit-8 (CCK-8), wound-healing, and transwell assays were employed, which collectively demonstrated that RAD54L promoted the proliferation and migration of HCC cells.Conclusion: RAD54L exhibits robust expression in both pan-cancer and HCC, exerting a significant influence on the proliferation and migration of HCC cells. These findings highlight its potential as a promising biomarker for pan-cancer and a prospective target for immunotherapy.Keywords: RAD54L, pan-cancer, tumor microenvironment, malignant behavior